PENGEMBANGAN VIDEO STOPMOTION ETNOMATEMATIKA CERITA RAKYAT BAWANG MERAH DAN BAWANG PUTIH PADA MATERI BILANGAN BULAT KELAS VII SMP - Abdul Karim; Risma Andayani; Riscka Nurul Fadilah; Maria Magdalena Bebhe; Mutmainah Safira; Marliah (CV. ADIBA AISHA AMIRA, 2024)
Research on the development of learning media in the form of stopmotion videos. Ethnomathematics of the folklore of shallots and garlic with the aim of increasing students' understanding of integer material in class VII of junior high school. The method used in this research is R&D (research and development) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The data collected in analyzing needs is by collecting various information regarding what is needed by junior high school students. To find out this is done by observing mathematics learning activities and conducting interviews with mathematics teachers who teach in junior high schools. The media feasibility test has been tested by several experts, providing input and suggestions for this stopmotion video learning media. With this learning media, it can provide a deeper understanding regarding the material of integers, which is a basic concept that must be mastered by students.